Chicken manure-based bioponics: Effects of acetic acid supplementation on nitrogen and phosphorus recoveries and microbial communities. (1st January 2022) - Wongkiew, Sumeth; Polprasert, Chongrak; Koottatep, Thammarat; Limpiyakorn, Tawan; Surendra, K.C.; Khanal, Samir Kumar
Graphical abstract: Highlights: Supplementation of acetic acid (500–1500 mg/L) decreased plant yields in bioponics. Acetic acid did not significantly affect N, P, and COD concentrations. Acetic acid affected some microbial OTUs and metabolic genes in the bioponics. Organic degradation and nutrient mineralization by microbes occurred symbiotically. Root microbes functioned symbiotically for nutrient transformation and recovery. Abstract: Bioponics has the potential to recover nutrients from organic waste streams, such as chicken manure and digestate with high volatile fatty acid (VFA) contents through crop production. Acetic acid, a dominant VFA, was supplemented weekly (0, 500, 1000, and 1500 mg/L) in a chicken manure-based bioponic system, and its effect on the performance of bioponics (e.g., plant yield and nitrogen and phosphorus availabilities) was examined. Microbial communities were analyzed using 16S rRNA gene sequencing, and the functional gene abundances were predicted using PICRUSt. Although acetic acid negatively affected plant yield, no significant difference ( p  > 0.05) was noted in the average nitrogen or phosphorus concentration. In terms of nutrient recovery, the bioponic systems still functioned well, although higher concentrations of acetic acid decreased plant yield and altered the bacterial communities in plant roots and chicken manure sediments. These data suggest that an acetic acid concentration of < 500 mg/L or a longer loading interval is recommended for the effective operation of chicken manure and digestate-based bioponics.